Real-world effectiveness of sofosbuvir/velpatasvir, glecaprevir/pibrentasvir, and sofosbuvir/velpatasvir/voxilaprevir against genotype 3 hepatitis C virus infection: a systematic review and meta-analysis - Liwei Zhuang; Liwei Zhuang; Junnan Li; Yu Zhang; Shibo Ji; Huichun Xing; Huichun Xing (Frontiers in Gastroenterology)
IntroductionDirect antiviral agents (DAAs) have dramatically changed the landscape of liver diseases associated with chronic hepatitis C virus (HCV) infection. However, limited data are available on the antiviral effect of sofosbuvir (SOF) + velpatasvir (VEL) ± ribavirin (RBV), SOF + VEL + voxilaprevir (VOX), and glecaprevir (GLE) + pibrentasvir (PIB) in treating patients infected with HCV GT3 in a real-world setting.MethodsUsing the EMBASE, PubMed, and Cochrane Library databases, articles were screened from 1 January 2016 to 1 June 2024. The sustained virologic response (SVR) rates were analyzed using the Freeman–Tukey double arcsine transformation in a random-effects model in R4.1.0 software.ResultsWe recruited 3,177 patients with HCV GT3 in 19 studies from 9 countries. The pooled SVR12/24 rate of the three evaluated regimens was 94.00% (95% CI: 90.87-96.59%). Furthermore, the SVR rate was 83.81% (95% CI: 75.70-90.62%) in patients receiving SOF+VEL+VOX; 94.98% (95% CI: 92.02-97.33%) in patients receiving SOF+VEL ± RBV; and 96.96% (95% CI: 93.20-99.45%) in patients receiving GLE+PIB. The pooled SVR12/24 rate of the three regimens was 95.70% (95% CI: 91.74-98.58%) and 90.50% (95% CI: 83.50-95.90%) in non-cirrhotic and cirrhotic patients, respectively. The pooled SVR rate was 96.79% (95% CI: 93.37-99.13%) and 88.41% (95% CI: 82.67-93.22%) in treatment-naive and treatment-experienced patients, respectively.ConclusionSOF+VEL ± RBV, GLE+PIB, and SOF+VEL+VOX had good antiviral effectiveness for chronic HCV-GT3 infection in real-world settings. Factors such as cirrhosis and treatment experience, especially previous DAA treatment failure, may influence the SVR rate.